Knowledge Transfer in Buyer-Supplier Relationships - When It (Not) Occurs - Werner Bönte; Lars Wiethaus (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2005)
Abuyer?s technical knowledge may increase the efficiency of its supplier. Suppliers, however, frequently maintain relationships with additional buyers. Knowledge disclosure then bears the risk of benefiting one?s own competitor due to opportunistic knowledge transmission through the common supplier. We show that in one-shot relationships no knowledge disclosure takes place because the supplier has an incentive for knowledge transmission and, in anticipation of this outcome, buyers refuse to disclose any of their knowledge. In repeated relationships knowledge disclosure is stabilized by larger technological proximity between buyers and suppliers and destabilized by the absolute value of the knowledge.
Keywords: L13; L20; O32; O31; 330; Knowledge Transfer; Knowledge Spillovers; Cooperation; Innovation; Repeated Games